Seroprevalence of Immunoglobulin G Antibody to Parvovirus B19 in Ontario. (1996) - Wasfy, Samia; Nishikawa, John; Petric, Martin
Abstract : The prevalence of antibody to parvovirus B19 was assessed in two populations. In a group of 494 residents from Ontario and the Maritimes, virus-specific immunoglobulin (Ig) M antibody, a marker of acute infection, was found throughout the year but was most prevalent during the late winter and early spring months. The overall prevalence of IgG antibody in this group was 30.3%. In an effort to examine age-specific prevalence in this population, a second group of sera from 210 pediatric patients at The Hospital for Sick Children, Toronto, Ontario and from Red Cross blood donors was tested for the presence of B19-specific IgG, and of these, 31.4% of the samples were positive. This prevalence varied from 3.3% in the under five-year-old age group to 66.7% in the 35- to 45-year-old age group. Eighty per cent of sera from females of this group were seropositive. This study provides insight into the prevalence of parvovirus B19 IgG antibody in the population.